Nutritional support in sepsis and septic shock - Weronika Wasyluk; Martyna Wasyluk; Agnieszka Zwolak; Robert Jan Łuczyk (Kazimierz Wielki University, 2019)
Sepsis is a life-threatening organ dysfunction caused by a dysregulated host response to infection. Its incidence is increasing worldwide. Sepsis and septic shock are associated with changes in metabolism. So far, research into nutrition and metabolism in sepsis has shown inconsistent results. Inadequate nutrition (both malnutrition and overfeeding) is detrimental for the patient. According to current recommendations, the treatment of choice in patients with sepsis is enteral nutrition, which is associated with many benefits. In the absence of enteral nutrition or the inability to provide the patient's energy requirements, total or partial parenteral nutrition is indicated. ESPEN guideline on clinical nutrition in the intensive care unit recommends for critically ill mechanically ventilated patients to assess energy expenditure by indirect calorimetry - in this case, hypocaloric nutrition is recommended in the early acute phase, and gradual introduction of isocaloric nutrition at a later stage. For critically ill patients, a progressive supply of 1.3 g/kg BW protein equivalents per day is recommended. The amount of carbohydrates should not exceed 5 mg/kg BW/ min. Intravenous lipid emulsions in parenteral nutrition should not exceed 1.5 g lipids/kg BW/day and should be adequate to the patient's tolerance. There is no clear evidence of the effect of supplementation with fish oil, antioxidants and glutamine on the results of treatment in patients with sepsis, none of these substances is indicated for routine use. More research is needed into the metabolism and nutrition of patients with sepsis.